Using Balanced Scorecard for Measuring “Baghdad Soft Drinks Company” Performance - May George Kassir; Reem Raad Jassim (Engineering and Technology Journal, 2016)
To expand and to achieve a market share, companies must have a clear policy to achieve their goals, and that cannot be done without measuring their performance from different perspectives and views because the financial perspective only cannot give a right view. Balanced Scorecard (BSC) is one of the performance measurement systems, and it is suitable measurement system that determines the performance, by the integration of all the financial and nonfinancial measures. The BSC was implementing in “Baghdad Soft Drinks Company” with its four perspectives for three years (2011 to 2013). The conclusions of BSC showed that for financial perspective the company has a clear growth according to the financial perspective measure's percentages, for customer perspective: the irregular percentage values of customer perspective measures indicate that the company needs to be more interactive with their customer requirements. But for internal business process perspective the company almost committed to the planned production, and has a good utilization and efficiency percentages, and for learning and Growth perspective the percentages explain the company does not commit to the budget-costs as planned.